Chitinase involved in immune regulation by mediated the toll pathway of crustacea Procambarus clarkii. Issue 110 (March 2021) - Liu, Min; Chen, Chen; Wu, Qi-Cheng; Chen, Jia-Le; Dai, Li-Shang; Hui Chu, Sheng; Liu, Qiu-Ning
Abstract: Chitinase can degrade chitin and play an essential role in animal immunity and plant defense. The immune functions of Chitinase in Procambarus clarkii ( P. clarkii ) remain to elucidate. Here, we identified PcChitinase 2 gene sequence from P. clarkii and studied its spatial and temporal expression profiles. The PcChitinase 2 transcribed unequally in different tissues; however, its expression was highest in those of stomach, gut, and hepatopancreas. The challenge with lipolysaccharide or peptidoglycan significantly up-regulated the expression of PcChitinase 2 in hepatopancreas. The knockdown of the PcChitinase 2 gene by double-stranded RNA suppressed most of the Toll-pathway-related immune genes ( phospholipase, lectin, sptazle Cactus, serine proteikinase, anti-lipopolysaccharide factor, and Toll ) production were significantly increased. Our results suggest PcChitinase 2 may be involved in the innate immune responses of P. clarkii by modulating the toll pathway. Highlights: A Chitinase 2 from Procambarus clarkii ( PcChitinase 2 ) was identified and characterized for the first time. The expression profiles of PcChitinase 2 in various tissues were investigated. Transcripts and expression levels of PcChitinase 2 in the hepatopancreas were detected after LPS and PGN challenge. RNA interference of PcChitinase 2 influenced the expression of immune-related genes.